2020
DOI: 10.1155/2020/1328436
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of the G-Protein-Coupled Receptor 4 in the Increased Expression of RANK/RANKL/OPG System and Neurotrophins by Nucleus Pulposus Cells under the Degenerated Intervertebral Disc-Like Acidic Microenvironment

Abstract: Intervertebral disc (IVD) degeneration is associated with local inflammation and increased expression of neurotrophins. Acidic microenvironment is believed to cause the progression of IVD degeneration. However, there is a paucity of information regarding the relationship between acidic microenvironment and the inflammation and expression of neurotrophins in IVD. G-protein-coupled receptor 4 (GPR4) is a pH-sensing receptor, which can activate the inflammation and increase the expression levels of nerve growth f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 38 publications
(48 reference statements)
0
6
0
Order By: Relevance
“…Previous studies demonstrated that other MMPs are regulated by an acidic condition in different diseases. The expression levels of MMP3 and MMP13 were elevated under the degenerated intervertebral disc-like acidic condition 34 . MMP12 is also increased by extracellular acidosis in systemic sclerosis 35 .…”
Section: Discussionmentioning
confidence: 94%
“…Previous studies demonstrated that other MMPs are regulated by an acidic condition in different diseases. The expression levels of MMP3 and MMP13 were elevated under the degenerated intervertebral disc-like acidic condition 34 . MMP12 is also increased by extracellular acidosis in systemic sclerosis 35 .…”
Section: Discussionmentioning
confidence: 94%
“…Previous studies demonstrated that other MMPs are regulated by acidic condition in different diseases. The expression levels of MMP3 and MMP13 were elevated under the degenerated intervertebral disc-like acidic condition 33 . MMP12 is also increased by extracellular acidosis in systemic sclerosis 34 .…”
Section: Discussionmentioning
confidence: 94%
“…Receptor activator of NFκB ligand was the important pathway involved in neurotrophins secretion by nucleus pulposus cells under the degenerated IVD-like acidic microenvironment 17 . We found that A2aR reduced when NP cells stimulated by IL-1β, meanwhile, cAMP and CREB downregulated but NFκB upregulated.…”
Section: Discussionmentioning
confidence: 99%